2010
DOI: 10.1029/2010wr009297
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent and advective momentum fluxes in streams

Abstract: [1] The scope of the present paper is the evaluation of the exchange of momentum in natural streams to explore the contribution that turbulence and secondary currents have on the shear stress distributions within the flow, and hence evaluate the overall hydraulic resistance. Existing methods for the evaluation of shear stresses in rivers are examined with respect to their applicability to complex flow fields, and a new mathematical formulation for analyzing the shear stresses affecting the longitudinal velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…() who evaluated Reynolds stress and associated sediment transport over a coastal foredune. Methods to derive τ using a modified TKE are used in fluvial geomorphology (Biron et al ., ; Pope et al ., ; Noss et al ., ) based on a linear relationship between TKE and τ (Soulsby and Dyer, ; Kim et al ., ). Research comparing TKE with τ _ LOW and τ _ REY has typically found that the TKE method is more suitable in complex flow conditions (Biron et al ., ; Bagherimiyab and Lemmin, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() who evaluated Reynolds stress and associated sediment transport over a coastal foredune. Methods to derive τ using a modified TKE are used in fluvial geomorphology (Biron et al ., ; Pope et al ., ; Noss et al ., ) based on a linear relationship between TKE and τ (Soulsby and Dyer, ; Kim et al ., ). Research comparing TKE with τ _ LOW and τ _ REY has typically found that the TKE method is more suitable in complex flow conditions (Biron et al ., ; Bagherimiyab and Lemmin, ).…”
Section: Discussionmentioning
confidence: 99%
“…In part, the predictive deficiencies may be attributed to methodological or technological limitations in measuring shear stress in natural boundary layer environments (Heathershaw and Simpson, ; Biron et al ., ; Noss et al ., ; Lee and Baas, ). Across the Earth sciences, however, improvements in sensor technology have provided methods for determining shear stress directly from turbulence statistics measured within the flow.…”
Section: Introductionmentioning
confidence: 97%
“…In low‐gradient small streams, Whiting [] and Noss et al . [] found that topographic forcing of the flow caused convective acceleration, which was the dominant component of the total momentum flux at lower stages, but was also not negligible at higher stages. Because depth and width are related to discharge and simultaneously provide the scale of the most effective roughness, the resistance strongly depends on the flow depth and on the riverbed topography at the corresponding length scales.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research quantified bed shear stress or the distribution of shear stress around the channel boundary (e.g. Wilcock, ; Biron et al ., ; Noss et al ., ; Nepf, ). Additional work modelled the distribution of boundary stress in prismatic channels with grain roughness as a function of channel cross‐sectional geometry, secondary flow structure, and friction at the channel boundary (e.g.…”
Section: Introductionmentioning
confidence: 99%